Development of Saccharomyces cerevisiae Y486–based biosensor carrying both CPR-CYP3A4 and DIN7-GFP constructs for mutagenicity testing of procarcinogens - Huyen, Nguyen Thi Thu; Ngoc, Bui Van (Vietnam Journal of Biotechnology, 2021)
In the world and Vietnam, a great number of toxic substances from industrial and agricultural activities, food production, and healthcare services are daily released into the environment. Many exogenous harmful substances are procarcinogens, but become carcinogens by the bioactivation of human cytochrome P450 enzymes (CYPs). Thus, development of analytical testing for rapid detection of procarcinogens plays a crucial role in food safety and environmental monitoring. This study aims to establish a biosensor basing on Saccharomyces cerevisiae Y486 cotransformed with two promoter–gene constructs, CYP3A4–CPR and DIN7–GFP. The results showed that all recombinant proteins were coexpressed in Y486 cells. The molecular weight of recombinant CPR and CYP3A4 were 75 kDa and 56 kDa, respectively. CYP3A4 enzyme only showed its catalytic activity in biotransformation of the specific substance as coexpressed with CPR. Kinetic constants, Km, Vmax, and Vmax/Km, of this CPR–CYP3A4 enzyme complex were 3.2 µM, 3.5 pmol/pmol CYP/min, and 1.1 μL/pmol CYP/min, respectively. Coexpressing constructs of CPR–CYP3A4 and DIN7-GFP in Y486 strain was able to identify aflatoxin B1 in the range of 0.1 - 0.4 µM; benzo(c)pyrene in the range of 10 - 40 µM. However, this system could not detect other procacinogens, such as, N-Nitrosodimethylamine, at any investigated concentrations. These findings were the first trial for further development of other biosensors to determine diverse procarcinogens in the enviroment by redesign of coexpressing constructs or replacement of the specific CYPs and inducible promoters.